Time-Dependent Spatial Amplitude Patterns of Harmonic Tremor at Arenal Volcano, Costa Rica: Seismic-Wave Interferences? - Almendros González, Francisco Javier (2012)
Seismograms recorded at the receivers of a small‐aperture seismic array usually display very similar waveforms and amplitudes, as a consequence of their close proximity. During the analysis of the volcanic tremor wave field at Arenal volcano, Costa Rica, we detected significant differences in the amplitudes of harmonic tremor recorded at the stations of a small‐aperture (∼210  m) seismic array. The amplitude distributions are geometrically complex and characterized by strong gradients. They occur just for harmonic tremors; any other type of seismic event produces nearly uniform amplitudes across the array. This suggests some relation with harmonic frequency content. Moreover, the spatial amplitude patterns change with time. Some of these observations could be explained by an extreme combination of source, path, and site effects. But they also could be produced by interference of different components of the seismic wave field. We use numerical calculations to investigate the amplitude pattern generated by two interfering plane waves, and are able to reproduce the main features of the observed amplitude patterns. We propose mechanisms that might generate seismic wave fields with multiple components and conclude that interference can explain the complexity and variability of the harmonic tremor wave field at Arenal volcano.